The effect of applying temperature stimulation to different positions in flexibility training of the hip joint - Zhang, P. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Flexibility is determined by the range of motion and the elasticity and extension ability of muscles, tendons and ligaments. Flexibility plays an important role in improving sport techniques. Good Flexibility is favourable in improving sports performance, decreasing the chance of sports injury, increasing the range of motion and in promoting coordination. Therefore, it is very important to develop flexibility for improved performance and reduction in injuries. Research has shown that the extensibility of muscles, tendons and ligaments is also related to temperature. This article is about the coordinating effect of flexibility training and temperature simulation to the improvement of hip joint` flexibility through flexibility training on hamstring and applying temperature stimulation to belly or tendon at the same time. Methods Fifty university students were divided into three groups randomly with equal ratios of males and females. The control group is composed of 14 students, the experimental group one (EO group) is 18 and the experimental group two (ET group) is 18. Stretch exercises were then applied to the hamstrings in the control group. Temperature stimulation was applied to the belly of the hamstrings in stretch exercises in the EO group, temperature stimulation was applied to tendon of hamstring in stretch exercises in the ET group. All three methods of stretching were identical. Every action was done 5 sets, each set lasts 45 seconds, and the interval between two sets is 15 seconds. Exercises were completed once a day, 3-4 days a week, for one month. Before and after the experiment, the ROMs of the flexion of hip joint, including active and passive ROMs of legs, are measured. Results After one month`s training, the values of sit and touch of all the control and the experimental groups increase significantly (P<0.01), and the values of sit and touch of both EO and ET groups increase more obviously than that of the control group (P<0.01). The ROMs of the flexion of hip joint, including active and passive ROMs of legs, in all the control and the experimental groups increase significantly (P<0.05). The range of increase of the active ROM of the flexion of right hip joint and passive ROM of the flexion of left hip joint in the EO group is significantly larger than that of the control group (P<0.05). The range of increase of the passive ROM of the flexion of left hip joint in the ET group is significantly greater than that of the control group (P<0.05). The range of increase of the ROMs of the flexion of hip joint in the EO group is significantly bigger than that of the ET group (P<0.05). Conclusions The results of this study showed that: (1) Stretching exercise training for one month can significantly improve the flexibility of hamstring muscles. (2) Applying temperature stimulation to stretch training can significantly increase the effect of the improvement in hamstring flexibility. (3) The effect of applying temperature stimulation to belly in flexibility training is better than the one that apply temperature stimulation to tendon.